Kondisi Sosial Ekonomi Masyarakat Pengrajin Sulaman Tangan di Nagari Jopang Manganti Kecamatan Mungka Kabupaten Lima Puluh Kota - lusi mawarni; Afdhal Afdhal (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
Abstrak This study aims to find out: (1) Level of education, (2) Income level, (3) Health conditions, and (4) Transportation conditions of hand-embroidery craftsmen in Jopang Manganti Nagari, Mungka District, Lima Puluh Kota Regency. The type of research used is using quantitative descriptive methods. The study population used was hand embroidery craftsmen in Jopang Manganti Nagari in Lima Puluh Kota Regency, which consisted of 28 hand embroidery craftsmen. The study sample consisted of saturated samples. Saturated withdrawal of hand embroidery craftsmen, 28 hand embroidery craftsmen. The technique of data collection is done by observation and questionnaires. The data analysis technique used is using percentages. The results showed that: (1) The level of education of hand embroidery craftsmen was classified as high with most of them graduating from high school (39.29), and many of their children were still in school and quite a lot were also dropping out of school. (2) The income of hand embroidery craftsmen is less than Rp. 1,500,000 per month (96.43%). (3) The health condition of the hand embroidery craftsmen is quite good, because the craftsmen are aware of the importance of health for them. If the embroidery craftsmen suffer from minor illnesses, the embroidery craftsmen go to the health center (60.71%), if the embroidery craftsmen suffer from severe illness the craftsmen go to the treatment also go to the puskesmas (82.14%). (4) The transportation conditions of embroidery craftsmen, namely craftsmen, mostly own motorized vehicles (82.14%) and the costs for transportation of craftsmen are Rp. 50,000-Rp. 80,000 per month (39.29%) of all respondents. Keywords: Socio-Economic Conditions, Embroidery Craftsmen